PEMANFAATAN TEKNOLOGI UNTUK MENINGKATKAN EKONOMI NELAYAN TUNA DI DUSUN TAPI DESA WAKASIHU - Waas, Harold J D; Wattimena, Marlin C; Krisye, Krisye; Rahman, Rahman; Saleky, Valentine D (Balobe: Jurnal Pengabdian Masyarakat, 2023)
Tuna fishing is one of the main livelihoods of the people of Wakasihu Village, in West Leihitu District. The impact of climate change and other external factors makes it difficult to determine potential tuna fishing areas in the waters. As a solution, the Department of Marine Science, Pattimura University has disseminated information on the Application of Satellite Remote Sensing and Acoustic Technology to Improve Fishermen's Economy. The results of the implementation of the activities were obtained (1) The desire of the tuna fishing community to use both technologies in tuna fishing operations, (2) Formation of a tuna fishing group to facilitate the processing of the KUSUKA Fisherman Card and obtaining assistance from the Marine and Fisheries Agency of Maluku Province, (3) Desire entered into an MoU with the Faculty of Fisheries and Marine Sciences, Pattimura University to solve fisheries problems in Wakasihu Village.